Study Some Angles Of Muscular Work in the Second division of Clean Jerk From Squat and Split - shboot , Ali; Salih , Mustafa (Journal of Physical Education, 2011)
The aim of the study is to to analyze the motor path of weight lifters during performance and to find the angles of muscular working the second division of clean jerk from squat and split and comparing between them.It also aimed at fining the most suitable way of performance for Iraqi weight Lifters so that they can perform with less effort and more success. The subjects of the research were fove Iraqi national League weight lifters.The wrer shot during performing the second division of clean jerk using both methods.The results were analyzed using special programs for motor analysis to find the angles of those weight lifters. After analyzing and disussing the variables for each weight lifter and for both methods the researchers came up with the following conclusions: 1. 70% of the subjects recorded the smallest angles for knee when bending whill 80% of the subjects recorded the smallest of torso angles and for the same phase.This indicates that the distance of weight lifters dip is bid to get more pushing and height and gaining height will lead to free dipping in turn (for each action there is an action equal in amount but in the opposite direction). 2. 90% of the subjects had larger angles in the torso in the extension phase of squat compared to split.That is to say in this phase,the weight was closer and thus more stable in the arms. 3. Most of the subjects recorded positive angles better using squat method and that shows that Iraqi weight lifters can perform squat clean jerk more accurately than the split method. 4. Not taking much distance for dipping in the split method ehich effects negatively upon the phases that follows. 5. Not using the proper method for each weight lifter. 6. The majority of the subjects were trying to increase the inclination of the torso to decrease the distance between the weight and the imaginary line. The researchers recommended the following: 1. The necessity of shooting international championships to find the mistakes and to study them by experts. 2. The importance of using proper exercises to correct mistakes in performance. 3. Specifying the proper method for each weight lifter that maybe other methods in other developed countries. 4. Focuing on concentration in motor performance in clean jerk and for both methods. Paying attention to the second divivion of the clean jerk especially for yong weight lifters to overcome mistakes as soon as possible .